RADICAL CONSTRUCTIVISM AND THEOLOGICAL EPISTEMOLOGY - Crosby, John F. (Essays in the Philosophy of Humanism, 2013)
Theology and religious beliefs, including issues dealing with theism, deism, creedal statements, dogma, and spiritualism are considered to be constructed reality. They are herein identified as first order truth. First order truth is personal truth and, as such, it becomes part of the reality of the believer. Constructed theological and religious belief is considered to be a legitimate part of radical constructivism irrespective of the validity and viability of the constructed reality. Second order truth, truth that is beyond the limits of human verification, is herein introduced as the term for ultimate ontological and metaphysical reality. As such, reality is neither denied nor is it attributed to a solipsistic mind. Ultimate and so-called metaphysical reality is unknowable in the epistemological sense of having the capability of being known in any empirical and verifiable manner. To the degree that ultimate and metaphysical reality is known, it is known only via the constructs of the human mind. Perceptions of reality that arise from rigorous empirical research, including experimental and observational data, are certainly to be considered valid, reliable, and viable, but never irreplaceable. In the practice of science and the scientific method there is always the possibility of new hypotheses and theories based on new experimentation and new data, and thus, a case may be made that all knowledge, even scientific and empirical knowledge, is tentative.